A new method of TX leakage cancelation in W/CDMA and GPS receivers - Aparin, V. (2008 IEEE Radio Frequency Integrated Circuits Symposium, 2008)
The theory and practical implementation of a novel TX cancelation method in CDMA and GPS receivers are described. The method is similar to the continuous-time LMS algorithm, but uses the TX LO as the reference signal and low-pass filters instead of the integrators. The method was implemented as part of a 0.18 mum CMOS cellular-band receiver to cancel the TX leakage at the LNA input. The measured maximum rejection of the TX leakage is approximately 20 dB, the LNA NF is 1.8 dB, and the dc current consumption of the TX canceler is 4 mA.